(untitled) (Comprehensive Journal of Science, 2026)
This study aims to evaluate the impact of the interaction between genetic and environmental factors on the productive performance of local sheep and goats in the Al-Jamil and Al-Asah regions, where animal production suffers from a significant decline due to a lack of understanding of the nature of this interaction. This study was conducted on 200 animals (100 sheep and 100 goats)The main local breeds (Berber, Arabian, Naeemi for sheep and Baladi, and Volcanic for goats) were distributed across three ecological levels according to the feeding system and the administrative level. Productive measurements (weights, growth rates, milk production, fertility) were monitored for 12-18 months. For this purpose, the statistical analysis used the mixed linear model and the interaction criterion model. The results showed statistically significant differences between the breeds in productive traits, with the Naeemi and Burkan breeds excelling in good nutritional conditions, while the Berber and Baladi breeds showed stability and acceptable production in harsh conditions. Despite the economic and social importance of this resource, scientific studies that have addressed the evaluation of the performance of these breeds under local environmental conditions are still rare, if not non-existent.